Inhibition of capsaicin‐driven nasal hyper‐reactivity by SB‐705498, a TRPV1 antagonist. (May 2014) - Holland, Carlijn; van, Cornelis; Denyer, Jane; Smart, Kevin; Segboer, Christine; Terreehorst, Ingrid; Newlands, Amy; Beerahee, Misba; Fokkens, Wytske; Tsitoura, Daphne C.
<x xml:space="preserve">Abstract</x> Aims To assess the safety, tolerability, pharmacokinetics (PK) and pharmacodynamics (PD) of intranasal SB‐705498, a selective TRPV1 antagonist. Methods Two randomized, double‐blind, placebo‐controlled, clinical studies were performed: (i) an intranasal SB‐705498 first time in human study to examine the safety and PK of five single escalating doses from 0.5 to 12 mg and of repeat dosing with 6 mg and 12 mg twice daily for 14 days and (ii) a PD efficacy study in subjects with non‐allergic rhinitis (NAR) to evaluate the effect of 12 mg intranasal SB‐705498 against nasal capsaicin challenge. Results Single and repeat dosing with intranasal SB‐705498 was safe and well tolerated. The overall frequency of adverse events was similar for SB‐705498 and placebo and no dose‐dependent increase was observed. Administration of SB‐705498 resulted in less than dose proportional AUC(0, 12 h) and Cmax, while repeat dosing from day 1 to day 14 led to its accumulation. SB‐705498 receptor occupancy in nasal tissue was estimated to be high (>80%). Administration of 12 mg SB‐705498 to patients with NAR induced a marked reduction in total symptom scores triggered by nasal capsaicin challenge. Inhibition of rhinorrhoea, nasal congestion and burning sensation was associated with 2‐ to 4‐fold shift in capsaicin potency. Conclusions Intranasal SB‐705498 has an appropriate safety and PK profile for development in humans and achieves clinically relevant attenuation of capsaicin‐provoked rhinitis symptoms in patients with NAR. The potential impact intranasal SB‐705498 may have in rhinitis treatment deserves further evaluation.